Association between serum zinc level and lipid profiles in children with spinal muscular atrophy - Long, Qi; Feng, Yijie; Chen, Fei; Wang, Wenqiao; Ma, Ming; Mao, Shanshan (Frontiers in Nutrition, 2022)
Background and aims Children with spinal muscular atrophy (SMA) have a high rate of dyslipidaemia, which is a risk factor of vital importance for cardiovascular diseases in adulthood. Studies have demonstrated that the serum zinc level is associated with lipid profiles in the general population as well as in individuals diagnosed with obesity or diabetes. The purpose of this study was to evaluate the relationship between serum zinc level and lipid profiles in children with SMA. Methods This cross-sectional study was launched in a tertiary children's medical center in China and involved pediatric patients with SMA under the management of a multidisciplinary team of outpatient services from July 2019 to July 2021. Anthropometric information, general clinical data, serum zinc level, lipid profiles, and body composition data were collected. Multivariate analysis was used for a thorough inquiry on the association between the serum zinc level and lipid profiles. Results Among the 112 patients with SMA [median (IQR) age 5.54 years (2.75–8.29), 58.04% female], who fulfilled the inclusion criteria of the study, dyslipidaemia was detected in 60 patients (53.57%). Based on multivariable linear regression, serum zinc level was positively associated with high-density lipoprotein cholesterol (HDL-C; β = 1.63, 95% CI = 0.44–3.22) and apolipoprotein A1 (APO A1; β = 2.94, 95% CI = 0.03–5.85) levels, independently of age, sex, type, activity, percentage of body fat, and body mass index. As the serum zinc level increased by 10 μmol/L, the risk of low APO A1 levels decreased by 35% (OR = 0.65, 95% CI = 0.44–0.97) according to multivariable logistic regression analyses. Conclusion Serum zinc concentration was positively correlated with HDL-C and APO A1 levels among children with SMA. We suggest measures to correct the lower level of serum zinc to improve HDL-C and APO A1 levels.